POSISI WAKIL MENTERI DAN IMPLIKASINYA TERHADAP BIROKRASI DI INDONESIA - Riris Katharina (Jurnal Politica, 2011)
The position of the vice ministers stipulated in Law Number 39 Year 2008 on The State Ministry raises a new problem. Phenomena such as the increasing of number of the vice ministers and the position of the vice ministers as career official but not part of cabinet but appointed by the President have been linked to their position as political appointee. The position of the vice ministers gives impact on bureaucracy in Indonesia. Focusing on the position of the vice ministers according to the law and its impact to bureaucracy, this paper recommends that the position of vice ministers in the future must be clear whether as political official or career official.